Role of sirtuins in bone biology: Potential implications for novel therapeutic strategies for osteoporosis - Li, Qiangqiang; Cheng, Jack Chun‐yiu; Jiang, Qing; Lee, Wayne Yuk‐wai (Aging cell, 2021)
The decline in bone mass and bone strength and musculoskeletal problems associated with aging constitute a major challenge for affected individuals and the healthcare system globally. Sirtuins 1‐7 (SIRT1‐SIRT7) are a family of nicotinamide adenine dinucleotide‐dependent deacetylases with remarkable abilities to promote longevity and counteract age‐related diseases. Sirtuin knockout and transgenic models have provided novel insights into the function and signaling of these proteins in bone homeostasis. Studies have revealed that sirtuins play a critical role in normal skeletal development and homeostasis through their direct action on bone cells and that their dysregulation might contribute to different bone diseases. Preclinical studies have demonstrated that mice treated with sirtuin agonists show protection against age‐related, postmenopausal, and immobilization‐induced osteoporosis. These findings suggest that sirtuins could be potential targets for the modulation of the imbalance in bone remodeling and treatment of osteoporosis and other bone disorders. The aim of this review was to provide a comprehensive updated review of the current knowledge on sirtuin biology, focusing specifically on their roles in bone homeostasis and osteoporosis, and potential pharmacological interventions targeting sirtuins for the treatment of osteoporosis. Sirtuins (SIRT1–SIRT7) are a family of nicotinamide adenine dinucleotide (NAD+)‐dependent deacetylases with remarkable abilities to promote longevity and counteract age‐related diseases. Sirtuins play diverse roles in bone homeostasis through actions on various cell types in bone tissues. Preclinical and clinical evidence have demonstrated the link between sirtuins and osteoporosis. Modulation of sirtuins could be potential strategies for the treatment of osteoporosis and other aging‐related bone disorders.